DETERMINING THE RELATIONSHIP BETWEEN CRITICAL THINKING DISPOSITION AND LIFE SATISFACTION, MEANING OF LIFE AND HAPPINESS LEVELS OF UNIVERSITY STUDENTS. - OZALP, Cemal (Journal of Health Sciences / Sağlık Bilimleri Dergisi, 2025)
This study was conducted to determine the relationship between university students' critical thinking tendencies and their life satisfaction, meaning in life and happiness levels. The data of the study were collected between 15 February and 15 April 2024. The sample of this study consisted of 1059 students studying at a state university. Descriptive information form, California Critical Thinking Scale, Satisfaction with Life Scale, Meaning of Life Scale and Oxford Happiness Scale were used to collect the data. 52.7% of the students were between 21-24 years of age, 79.2% were female, 24.4% were studying in the department of nursing, 46.2% were in the second year and 61% were living in dormitories. The students scored 235.14±26.39 points from the California Critical Thinking Scale, 18.47±6.31 points from the Satisfaction with Life Scale, 47.77±9.53 points from the Meaning of Life Scale and 21.74±4.34 points from the Oxford Happiness Scale-Short Form. As a result of multiple regression analysis, it was determined that there was a significant relationship between the Meaning of Life Scale and Oxford Happiness Scale-Short Form and California Critical Thinking scores. There is a statistically significant, positive and low-level relationship between California Critical Thinking Scale score and Satisfaction with Life Scale, Meaning of Life Scale and Oxford Happiness Scale-Short Form score. This study can be used in educational activities for the development of critical thinking skills in nursing and health sciences programmes and in the organisation of activities to support students' search for meaning.